Faith Character Education: Children's Moral Reinforcement in the Latent Phase - Azwar Rahmat; Fathor Rozi; Faizatul Widat; Umi Kulsum; Anita Puspadewi (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The moral degradation of the nation's children is increasingly concerning. Fights and bullying often occur in the school environment. Therefore, the values of the character of faith are very important to be instilled from an early age. This study aims to analyze the innovations used in shaping the morale of early childhood at RA Baitul Muttaqin Glagah-Pakuniran through faith character education. This study uses a qualitative approach to the type of case study. The location of this research is RA Baitul Muttaqin Glagah-Pakuniran. Data collection was obtained through documentation observation and interviews. Data analysis was carried out in three stages, namely data reduction, data display and conclusions. The results of this study RA Baitul Muttaqin Glagah-Pakuniran in order to shape children's morals through faith character education by implementing several special activities, namely the habituation of memorizing thoyyibah sentences and short letters, friday fitri, habituation of the practice of ABAS prayers (Let's Learn to Pray) and habituation of reading prayers 'a and asma'ul husna. In carrying out this activity the school works closely with parents of students to continue to practice the habits that have been taught at home and to set a good example for their children at home. Instilling character education through some good habituation of faith can realize the goals of national education which are the noble ideals of the state to be devoted to God and not only develop cognitive aspects but affective and psychomotor aspects of children.